The Evolution of Dispute Resolution, Negotiation, and Mediation in Greece - Karassavidou, Eleonara; Markovits, Yannis (Relations industrielles / Industrial Relations, 1996)
In this paper, a four-phase theory of industrial relations evolution is formulated so as to obtain a deeper understanding of contemporary deuelopments in industrial relations, as well as to situate the pattern of Greek industrial relations prior to 1990. Greece initiated a "U-turn " in its industrial relations system in the 1990s. The institutionalization of free collective bargaining, third party intervention on a voluntary basis, and the establishment of the Organization of Mediation and Arbitration (OMED) form the core of the new status quo in employee-employer relations in Greece. A general evaluation of the three years' experience of OMED indicates that a gradual, positive change in the atmosphere of the Greek industrial relations appears to have taken place. However, the transition from a long-standing low-trust and authoritarian industrial relations pattern requires the diffusion of new knowledge and experience, changes in cultures and support from multiple sources.